Pengaruh Kualitas Pelayanan Bartender Terhadap Kepuasan Pelanggan di D’Nest Bar & Grill Crown Vista Hotel Batam - Rais, Syafruddin; Ambiyar, Ambiyar (Universitas Pelita Harapan Medan, 2019)
Given the importance of the bar in providing the service of drinks, then the bar is required to have standard operating procedures in providing service drinks to guests so that between the one with the other will get the same service without difference. It is very helpful at all in the national program service provided so expected guests will get compliance with wishes and avoid complaints (complaint). So the authors are interested in researching the influence of the quality of service Bartenders Against customer satisfaction in D'Nest Bar Grill & Crown Vista Hotel Batam